Solution Observation of Dimerization and Helix Handedness Induction in a Human Carbonic Anhydrase–Helical Aromatic Amide Foldamer Complex. (4th March 2016) - Jewginski, Michal; Fischer, Lucile; Colombo, Cinzia; Huc, Ivan; Mackereth, Cameron D.
Abstract: The design of synthetic foldamers to selectively bind proteins is currently hindered by the limited availability of molecular data to establish key features of recognition. Previous work has described dimerization of human carbonic anhydrase II (HCA) through self‐association of a quinoline oligoamide helical foldamer attached to a tightly binding HCA ligand. A crystal structure of the complex provided atomic details to explain the observed induction of single foldamer helix handedness and revealed an unexpected foldamer‐mediated dimerization. Here, we investigated the detailed behavior of the HCA–foldamer complex in solution by using NMR spectroscopy. We found that the ability to dimerize is buffer‐dependent and uses partially distinct intermolecular contacts. The use of a foldamer variant incapable of self‐association confirmed the ability to induce helix handedness separately from dimer formation and provided insight into the dynamics of enantiomeric selection. Abstract : Interaction insights : Foldamer–protein interactions and dynamics were investigated in solution by NMR and circular dichroism. Protein‐induced foldamer handedness induction and foldamer‐mediated protein dimerization were shown to be largely independent processes. Distinct foldamer–protein interactions exist in monomeric and dimeric complexes.